Social networks in livestock and cacao value chains in the Colombian Amazon - Guáqueta-Solórzano, Victoria; Rodriguez, Luz A.; Ayazo, Roger; Vanegas, Martha (2025)
In this study we explore the structure of social relationships (actors and networks) that drive cacao and livestock food systems in the municipalities of Belén de los Andaquíes and La Montañita, in Caquetá.